KF Sensor-Based Honeypot against Hacker Attacks using Kali Linux on a Laptop - Ronald Wijoyo, Albert; Ahmad Fauzan Ritonga; Naufal Syafiq; Rafi Dzikra; Firza Ilham Pratama (Indonesian Journal of Electrical Engineering and Electronics, 2024)
This research analyzes the effectiveness of using KF Sensor-based honeypots in detecting and mitigating hacker attacks using Kali Linux on a laptop. A honeypot is a security system designed to attract and study cyber-attacks by deceiving attackers into believing they have accessed a vulnerable system. KF Sensor, as a type of honeypot, serves as bait to monitor malicious activities and collect attack data. This research employs an experimental method by configuring KF Sensor on a laptop targeted by attacks from Kali Linux. The results show that KF Sensor is effective in detecting various types of attacks, such as port scanning, brute force attacks, and exploit attempts. The data collected by KF Sensor provides valuable insights into the techniques and strategies used by attackers, as well as aids in strengthening overall system security. This study concludes that implementing a KF Sensor-based honeypot is a proactive and beneficial step in enhancing network security and protecting systems from cyber threats.